2012
DOI: 10.1007/s10562-012-0826-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of SnO2 Nanostructures and Their Application for Hydrogen Evolution Reaction

Abstract: SnO 2 hierarchical architectures were synthesized with a surfactant-free hydrothermal synthesis route. We found that the acid or alkaline amount (HCl or NaOH) of the solution had a remarkable effect on the morphology of as-synthesized products. The SnO 2 nanostructures were selected as a support of Pt catalyst (Pt/SnO 2 ) for hydrogen evolution reaction (HER) in the acidic media. The influence of SnO 2 morphologies on the electrochemical performance has been investigated by cyclic voltammetry and linear sweepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Finally, although the page numbers are certainly 98-100, the incorrect starting page 96 is used in all but one of the papers cited here. [6][7][8][9][10][12][13][14] It is clear that from the outset, Scherrer's paper was cited with errors and these errors were copied from paper to paper. This situation has culminated in the 'birth' of a fictitious co-author -N.G.W.…”
Section: Affiliationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, although the page numbers are certainly 98-100, the incorrect starting page 96 is used in all but one of the papers cited here. [6][7][8][9][10][12][13][14] It is clear that from the outset, Scherrer's paper was cited with errors and these errors were copied from paper to paper. This situation has culminated in the 'birth' of a fictitious co-author -N.G.W.…”
Section: Affiliationmentioning
confidence: 99%
“…Therefore it is of interest that a significant and growing number of recent articles attribute the original paper to two authors: P. Scherrer and N.G.W. Gottingen, [6][7][8][9][10][11][12][13][14] although it is clear from a digitised version of the original article ( Figure 1) 15 that Scherrer is the only author. The original paper is in German and a clue to the identity of the enigmatic co-author N.G.W.…”
mentioning
confidence: 99%
“…Zhang et al [208] reported the direct growth of 3D SnO2 dendrites with 1D nanorods as constituent nanostructures from a basic water-ethanol mixed solutions by using Na2SnO3·3H2O as the precursor reagent. Hierarchical SnO2 nanospheres were also synthesized from Na2SnO3·3H2O aqueous solutions [209].…”
Section: Direct Growth Of 3d Nanostructuresmentioning
confidence: 99%
“…The selection criterions of the alternative electrode for water electrolysis include low hydrogen over-potential, high electrocatalytic activity, high electrical conductivity, electrochemical stability, and reasonable cost. Alloying is a common approach to improve the intrinsic activity of hydrogen evolution of metal electrodes [ 5 ]. In particular, nickel and its alloys are well-known non-precious metal electrocatalysts for hydrogen production in alkaline electrolytes because of their special corrosion resistance and highly intrinsic electrocatalytic activity toward HER.…”
Section: Introductionmentioning
confidence: 99%